Protective Effect of Cordycepin on Experimental Testicular Ischemia/Reperfusion Injury in Rats. (2nd January 2018) - Okur, Mehmet Hanifi; Arslan, Serkan; Aydogdu, Bahattin; Zeytun, Hikmet; Basuguy, Erol; Arslan, Mehmet Serif; Ibiloglu, Ibrahim; Kaplan, Ibrahim
ABSTRACT: Objective: To investigate the role of cordycepin in testicular ischemia/reperfusion injury in rats. Materials and methods: Forty Wistar albino rats were randomly divided into four groups, as follows: group one, control (C); group two, torsion and ischemia (I); group three: detorsion with ischemia–reperfusion (IR); and group four, detorsion/cordycepin. The rats were then analyzed macromorphologically and histopathologically, and blood tests were performed. Specifically, the total oxidant status (TOS) and total antioxidant status (TAS) were determined, and malondialdehyde (MDA), tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β levels were analyzed. In addition, pyknotic nuclei, spermatozoa, edema, and hemorrhage were assessed. Results: When the IR and cordycepin groups were compared with the other groups, there was a statistically significant decrease in TNF-α and MDA levels ( p < 0.05). Increased TAS levels were observed in the cordycepin group compared with the control group. TOS levels were significantly increased in the I and IR groups, but decreased in the cordycepin group ( p < 0.05). Similar effects were observed in tissue biochemistry analysis. Histopathological evaluations revealed that the spermatozoa count was decreased in the I and IR groups. However, there was an increase in the cordycepin group, as well as a statistically significant difference between the IR and cordycepin groups ( p < 0.01). Finally, edema and inflammation were increased in the I and IR groups, but decreased in the cordycepin group. Conclusions: Histological and biochemical findings revealed that cordycepin protected against IR-induced testicular injury.